Detection of SST Wake in Belitung Island Induced by The Monsoon Wind. (June 2018) - Hariyadi; Wirasatriya, Anindya; Marwoto, Jarot; Taufiq-Spj, Nur; Currie, Destina Verika
Abstract: The Java Sea is one of the monsoon wind path blowing over Indonesia Seas. Belitung Island is located in the center of the monsoon path in the Java Sea. Although the topography Belitung Island relatively flat, the existence of mountainous with 200-300m height in the center of the Island may form the island wake during the strong wind event. Island wake phenomena in Belitung Island was investigated by using MODIS SST Lv3. From 2003 to 2016 period of observation, 245 cases of SST wake were found with the distribution for each season are 39, 35, 135 and 36 cases for NW monsoon, Transition I, SE monsoon and Transition II, respectively. The direction of SST wake depends on the direction of the surface wind. During NW monsoon and Transition I, the direction of SST wake is southeastwardly while during SE monsoon and Transition II is northwestwardly. The high Chl-a concentration outside the SST wake patch indicates that the occurrence of SST wake in the seas of Belitung Island may influence biological productivity in that area.